MYST3/CREBBP Rearranged Acute Myeloid Leukemia after Adjuvant Chemotherapy for Breast Cancer - Arjun Gupta; Mrinal M. Patnaik; Harris V. Naina (Case Reports in Oncological Medicine)
Although rare, clinicians and patients must be aware that therapy related malignancies, specifically acute myeloid leukemia (AML), can occur as a complication of adjuvant chemotherapy for breast cancer. Vigilance for signs and symptoms is appropriate. AML with t (8;16) is a specific translocation leading to formation of a fusion protein (MYST3/CREBBP). The MYST3/CREBBP AML tends to develop within 2 years of adjuvant chemotherapy, especially for breast cancer, without preceding myelodysplasia. It usually presents with disseminated intravascular coagulation and osteolytic lesions and has a poor prognosis despite aggressive resuscitation and therapy. With the increasing use of adjuvant chemotherapy for breast cancer, we are seeing a definite increase in the incidence of therapy related myelodysplastic syndromes and AML. One must keep this complication in mind while counseling and following up breast cancer patients who have received adjuvant chemotherapy. New osteolytic bone lesions in a patient with history of breast cancer do not necessarily mean metastatic disease and should be fully evaluated.